Main Character's Traumas in Kiyoshi Matsuda’s Re-main Anime: A Psychoanalytic Study - Nurul Septianingtyas; Ayu Putri Seruni (Universitas Cokroaminoto Palopo, 2022)
The purpose of this study was to determine a systematic study, reality versus neurosis and fixation on trauma contained in the main character of the anime RE-MAIN. The main character of the anime Re-main is Kiyomizu Minato. Kiyomizu Minato is a Yamanami High School student and water polo athlete. Minato has a pretty good performance ability. Yamanami High School is door to Rikka Academy. Minato before enrolling into Yamanami High School, he had already apply to Rikka Academy. Rikka Academy is famous for being an elite school for literature and martial arts.This is motivated by traumatic events that are around the environment and the people closest to them. In the last two years, there have been many variants of Covid-19, a natural disaster so that the incident caused a loved one to leave him. However, trauma in the film RE-MAIN uses the theory of Bessel A van der Kolk and Alexander C. McFarlane both from a systematic study, reality versus neurosis and fixation on trauma. This research method used is descriptive qualitative with content analysis technique with literary psychology approach. From the result of the analysis, it is known that in systematic study of trauma, it is found that there is an initial onset of trauma, reality versus neurosis, it is found that there is a daily reality and there is often a sense of anxiety disorder, and fixation on trauma results in a feeling of being obsessed with the trauma.